Quality of life of geriatric population in rural block of Haryana - Meena Rajput; Pinki Pinki; Sunil Kumar; Jaiprakash Jaiprakash; Tarun Kumar (Public Health Review: International Journal of Public Health Research, 2019)
Background: Population ageing refers to increasing share of older persons which has poised to become one of the most significant social transformations of the twenty-first century. This study aims to assess quality of life (QOL) of elderly in rural area.Methods: This was an observational study with cross-sectional design carried out in 400 elderly participants (60 years and above) in a rural area of district Jhajjar, Haryana. WHOQOL-BREF scale was used. Data entry and analysis was performed using SPSS version 20.0.Results: More than half (55%) of the study participants were in the age group of 60-65 years. 52.5% participants were females. Mean score of environmental domain was highest (62.72±14.18), followed by physical health domain (60.77±15.82). The domain which had the least mean score was social relationships (51.98±18.61). Mean scores of males in all domains were found higher than females and the difference in mean score was statistically significant (p < 0.05), which indicates better QOL of males compared to females.Conclusions: Most of the elderly people (53.8%) had average quality of life. Most of the females (64.8%) had average and 47.9% males had good quality of life. The subjects who were illiterate, financially dependent, having any health problem, of lower socio-economic class, living without partner, unemployed/homemaker had poor quality of life.